Analisis Analisis Semiotika dalam Siaran Televisi Sekitaran Etam di TVRI Kalimantan Timur - Alistia, Rafita; Indrahastuti, Tri; Ulwatunnisa, Marwah (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2024)
This research aims to explain and describe the elements of semiotic theory by C.S. Pierce (icon, index, and symbol) in the Television Broadcast Sekitaran Etam for the November 2022 Period on TVRI East Kalimantan. The Sekitaran Etam uses the Kutai language with the Tenggarong dialect. This broadcast discusses the culture and local wisdom of the people of East Kalimantan. The method used in this research is a qualitative research method. Data and data sources in this research are quotes containing icons, indexes, and symbols in the script Sekitaran Etam for the November 2022 period on TVRI East Kalimantan. The data analysis technique uses qualitative research techniques, according to Miles and Huberman, namely data reduction, data presentation, and concluding/verification. The research results on television broadcasts Sekitaran Etam for November 2022 on TVRI East Kalimantan found five data. Based on the five data found, eight icons, eight indexes, and seven symbols exist